Case Report: Etoposide-nedaplatin induced rhabdomyolysis in a small cell lung cancer patient - Xu, Xiaohu; Wu, Xiao; Zhang, Mingmin; Wang, Qi (Frontiers in Pharmacology, 2023)
Rhabdomyolysis syndrome refers to the breakdown and necrosis of muscle tissue caused by various reasons and the release of intracellular contents into the blood stream, which can seriously lead to acute renal failure or even death. In this article, we described for the first time a case report of severe rhabdomyolysis induced by etoposide-nedaplatin chemotherapy in a small cell lung cancer (SCLC IIIb) patient. He developed progressive general muscle pain and weakness after the first cycle of chemotherapy, accompanied by elevated creatine kinase (CK), myoglobin (Mb), alanine aminotransferase (ALT), spartate aminotransferase (AST) and lactate dehydrogenase (LDH). Examination and inquiry of medical history were used to exclude the factors of rhabdomyolysis caused by trauma, strenuous activities, infections, drugs, hyperthermia and immunity, the patient was diagnosed with severe rhabdomyolysis induced by chemotherapy. After treatment with intravenous fluids and methylprednisolone, the patient's symptoms were relieved and laboratory tests were significantly improved. An unexpected situation is that the lung CT scan showed that the lung mass was significantly smaller than that before chemotherapy, but the reason is not clear. Rhabdomyolysis induced by anti-cancer drugs, especially chemotherapy drugs, is rarely reported and easily overlooked. Therefore, physicians should be aware of this rare but potentially serious complication when using chemotherapy drugs.